A critical review and assessment for usage of recycled aggregate as sustainable construction material. (30th January 2017) - Kisku, N.; Joshi, H.; Ansari, M.; Panda, S.K.; Nayak, Sanket; Dutta, Sekhar Chandra
Highlights: Recycled Concrete Aggregate (RCA) is a future material towards sustainable development. Properties of Recycled Aggregate Concrete (RAC) and its performances are comprehensively documented. Advanced mixing approaches and incorporation of mineral additives for improving the properties of RAC. Abstract: The ever increasing population and urbanization has led to construction of high rise structures and demolishing existing old low rise ones. This has become not only the cause of natural resources depletion at an alarming rate but also gradually becoming a challenge for sustainability. Concrete industry consumes a majority of natural resources especially in developing countries. In recent years the concrete industry has started using Construction and Demolition (C&D) waste in structural concrete application owing to the availability of waste from demolition of old structures and the reduction in cost of acquiring aggregates. This can allow the concrete industry to reduce its carbon footprint and thus help it to continue to grow without harming the environment. In this backdrop, this paper provides an account of properties of concrete prepared with recycled aggregate, analyses the important findings on Recycled Aggregate Concrete (RAC) in the recent time and discusses the suitability of its usage in construction. The open literature suggests that the durability and mechanical properties of RAC is slightly inferior than that of conventional concrete. However, with the use of admixtures and modified mixing approaches, the desired properties of RAC can be obtained. Collation and analysis of more than 200 research papers in this area on various facts of Recycled Aggregate Concrete, on one hand, may be considered as a step ahead for formation of design methodology and, on the other hand, a valuable stating document for further research.